Connecting smallholder farmers to local markets: Drivers of collective action, land tenure and food security in East Chad. (November 2017) - Corsi, Stefano; Marchisio, Laura Viviana; Orsi, Luigi
Abstract: The paper deals with the drivers influencing smallholder farmers' access to local markets in developing countries, assuming that collective actions along with food security and land tenure are related and interconnected aspects that could facilitate market access. Data were collected in 26 Chadian villages in the Sila region; 98 questionnaires were submitted to peanut and sesame farmers belonging to associations. An ordered logistic regression was adopted to estimate our model where the dependent variable, access to market, is operationalized in terms of perceived improvement to market access. Our research contributes to the present understanding of the determinants of market access and its links with collective actions, land and food security through a comprehensive view of association support activities, structural features and household assets. Our main findings highlight that the role of secure land tenure is crucial in order to achieve a better access to local markets, confirming that strong relationships within local value chain stakeholders have positive effects on the capability to sell products, whereas the role of food security is circular: the more food secure a farmer is, the more he or she has access to markets but on the other side access to markets guarantees a higher food security.